Shrimp Digestive Bacteria Performance for Shrimp Waste Chitin Extraction - Kristina Novalina Nainggolan; Yudha Perdana Putra; Evi Fitriyani (Biology, Medicine & Natural Product Chemistry, 2024)
Generally, chitin is isolated chemically. An environmentally friendly alternative to chitin extraction is enzymatic extraction. The research aims to determine the effectiveness and optimum conditions for enzymatic chitin extraction of shrimp waste (heads, shells, and tails) using lactic acid bacteria (LAB) and proteolytic bacteria from the shrimp's digestive tract (faeces and intestines). The research stages were isolation, enrichment, and determining shrimp digestion's bacterial colonies, microscopic identification of shrimp digestive bacteria, and determining the effectiveness and optimal conditions for shrimp waste's chitin isolation. Aerobic and Anaerobic Total Plate Count (TPC), LAB, and proteolytic bacteria from shrimp's digestive tract per gram of sample were respectively 5.52 and 5.59 log CFU; 4.76 and 4.56 log CFU; 6.46 and 6.20 log CFU. Microscopic morphology shows that LAB and proteolytic bacteria of shrimp digestive are gram-positive as cocci or rods. The deproteinization value of shrimp waste reached 31%, especially for treatment with a pH of 5.0–7.0 (during proteolytic bacteria fermentation) and pre-treatment of boiling, drying and coarse grinding of shrimp waste (PP2) before extraction. However, the demineralization value of shrimp waste is only 4.5% (PP1) and 3% (PP2), with LAB as the primary fermentation agent because proteolytic bacteria have been unable to reduce the mineral content in shrimp waste further.